Comparison of outcomes of salvage robot‐assisted laparoscopic prostatectomy for post‐primary radiation vs focal therapy. (3rd October 2019) - Onol, Fikret Fatih; Bhat, Seetharam; Moschovas, Marcio; Rogers, Travis; Ganapathi, Hariharan; Roof, Shannon; Rocco, Bernardo; Patel, Vipul
Abstract : Objectives: To compare salvage robot‐assisted laparoscopic prostatectomy (RALP) outcomes in patients who underwent radiation and those who underwent focal ablation as primary therapies. Patients and Methods: We evaluated 126 patients who underwent salvage RALPbetween 2008 and 2018. Of these, 94 (74.6%) received radiation and 32 focal ablation (25.4%) as primary therapy. These groups were compared with regard to clinical, oncological and functional outcomes. Kaplan–Meier curves and regression models were used to identify survival estimations and their predictors. Results: Before surgery, more patients were potent in the focal ablation group compared to the radiation group (46.9% vs 22.6%; P = 0.013). Peri‐operative characteristics and complication rates were not significantly different between the two groups. Postoperative catheterization duration was shorter in the focal ablation group (mean 10 vs 16 days; P = 0.018). At final pathology, the focal ablation group had higher non‐organ‐confined disease (71% vs 50%; P = 0.042) and positive surgical margin (PSM) rates (43.8% vs 17%; P = 0.004) as compared to the radiation group; however, 5‐year biochemical recurrence (BCR)‐free survival rates were similar (59% vs 56%; P = 0.761). Postoperative 1‐year full (no pads/day) and social (0–1 pad/day) continence rates were significantly higher in the focal ablation as compared to the radiation group (77.3% vs 39.2%, P = 0.002, and 87.5% vs 51.3%, P = 0.002, respectively). Multivariate analyses showed primary focal ablation and nerve‐sparing to be predictors of postoperative continence. Erectile function was preserved in 13% and 27% of preoperatively potent patients in the radiation and focal ablation groups, respectively ( P = 0.435). No predictors were identified for postoperative potency. Conclusions: Radiation was associated with inferior functional outcomes after salvage RALP. Focal therapies were associated with higher non‐organ‐confined disease and PSMrates, with no significant difference in short‐term BCR‐free survival.